2023
DOI: 10.3390/su15108151
|View full text |Cite
|
Sign up to set email alerts
|

Abiotic and Biotic Effects on Microbial Diversity of Small Water Bodies in and around Towns

Abstract: Microbial communities play very important roles in pollutant treatment and absorption and material and energy cycling in wetlands. Among different wetland types, wetlands in and around towns are the most closely related to human life, but how human activities affect microbes in small water bodies has received little attention. In this study, nine small water bodies of three different landscape types were chosen in the Lishui District of Nanjing City, China. The microbial community characteristics of four diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…The differences in colony morphology indicated that bacteria isolates stemmed from various species [42]. Factors that affect variations in shape, color, and general morphological characteristics of bacteria include age, certain growth requirements, environment (biotic and abiotic), food (growth medium), temperature, pH, and free oxygen [43,44]. According to Zuraidah et al [45], the environmental conditions of bacteria life may cause changes in the morphological and physiological properties.…”
Section: Morphology Of Bacteria In Rice-fish Farming System Sedimentsmentioning
confidence: 99%
“…The differences in colony morphology indicated that bacteria isolates stemmed from various species [42]. Factors that affect variations in shape, color, and general morphological characteristics of bacteria include age, certain growth requirements, environment (biotic and abiotic), food (growth medium), temperature, pH, and free oxygen [43,44]. According to Zuraidah et al [45], the environmental conditions of bacteria life may cause changes in the morphological and physiological properties.…”
Section: Morphology Of Bacteria In Rice-fish Farming System Sedimentsmentioning
confidence: 99%